A novel cold-active GH8 xylanase from cellulolytic myxobacterium and its application in food industry. (1st November 2022) - Li, Xu; Zhang, Lei; Jiang, Zhitong; Liu, Lin; Wang, Jihong; Zhong, Lingli; Yang, Tao; Zhou, Qin; Dong, Weiliang; Zhou, Jie; Ye, Xianfeng; Li, Zhoukun; et al.
Highlights: XynSc8 from myxobacteria is a novel cold-active GH8 member. XynSc8 displays high hydrolysis efficiency at 4 and 50 °C. XynSc8 hydrolyzes xylan into xylooligosaccharides with degree of polymerization more than 3. XynSc8 improves specific volume and quality of bread at a low dosage (0.05–0.2 mg/kg). Abstract: Although xylanase have a wide range of applications, cold-active xylanases have received less attention. In this study, a novel glycoside hydrolase family 8 (GH8) xylanase from Sorangium cellulosum with high activity at low temperatures was identified. The recombinant xylanase (XynSc8) was most active at 50 °C, demonstrating 20% of its maximum activity and strict substrate specificity towards beechwood and corncob xylan at 4 °C with V max values of 968.65 and 1521.13 μmol/mg/min, respectively. Mesophilic XynSc8 was active at a broad range of pH and hydrolyzed beechwood and corncob xylan into xylooligosaccharides (XOS) with degree of polymerization greater than 3. Moreover, incorporation of XynSc8 (0.05–0.2 mg/kg flour) provided remarkable improvement (28–30%) in bread specific volume and textural characteristics of bread compared to commercial xylanase. This is the first report on a novel cold-adapted GH8 xylanase from myxobacteria, suggesting that XynSc8 may be a promising candidate suitable for bread making.